2016
DOI: 10.1007/s00262-016-1865-y
|View full text |Cite
|
Sign up to set email alerts
|

Reduced potency of cytotoxic T lymphocytes from patients with high-risk myelodysplastic syndromes

Abstract: Although phenotypically defined CTL numbers were increased in the bone marrow of MDS patients, we found that CTL from high-risk MDS patients exhibited a lower TCR-induced redirected cytotoxic capacity. Thus, decreased T cell cytotoxicity seems related to reduced adhesion to target cells and may contribute to impaired anti-leukemic immune surveillance in MDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 43 publications
1
7
0
1
Order By: Relevance
“…After recognition of tumor antigens presented by tumor cells through their MHC class I, activated CD8 + T cells release cytotoxic molecules leading to tumor cell apoptosis [ 96 ]. In the BM of MDS patients, a decrease in CD8 + T-cell cytotoxicity has been observed [ 97 , 98 ]. This loss of cytotoxicity is confirmed by the observation of an exhausted-like phenotype of bone marrow CD8 + T cells in MDS.…”
Section: Abnormal Immune Cell Repartition And/or Functions During The...mentioning
confidence: 99%
“…After recognition of tumor antigens presented by tumor cells through their MHC class I, activated CD8 + T cells release cytotoxic molecules leading to tumor cell apoptosis [ 96 ]. In the BM of MDS patients, a decrease in CD8 + T-cell cytotoxicity has been observed [ 97 , 98 ]. This loss of cytotoxicity is confirmed by the observation of an exhausted-like phenotype of bone marrow CD8 + T cells in MDS.…”
Section: Abnormal Immune Cell Repartition And/or Functions During The...mentioning
confidence: 99%
“…MDS blasts in high-risk diseases overexpress PD-L1 in comparison to normal controls [ 78 ] and this can be further augmented by the effects of cytokines, such as TNF-a, and IFN-γ, which induce PD-1 and PD-L1 expression, on T-cells and MDS cells, respectively [ 79 ]. Interestingly, Sand et al reported increased numbers of BM cytotoxic T-cells; however, they were accompanied by dysfunctional T-cell receptor (TCR) cytotoxicity [ 80 ].…”
Section: The Immune Landscape In Mdsmentioning
confidence: 99%
“…Drugs widely used for MDS have lately been shown to affect T‐cell polarization, which may suggest effects on MDSCs activity. Azacitidine, the drug of choice in high‐risk MDS, has been shown to affect T‐cell polarization in the Th17/Treg‐axis in high‐risk MDS and to influence levels of BM CD57 + T‐cells, CD57 + T‐cell degranulation and CD34 + BM cell directed cytotoxicity 34,35 . Specific MDSC‐targeting in MDS has so far been aiming at CD33‐expressing cells 36 .…”
Section: Myelodysplastic Syndromesmentioning
confidence: 99%
“…Azacitidine, the drug of choice in high-risk MDS, has been shown to affect T-cell polarization in the Th17/Treg-axis in high-risk MDS and to influence levels of BM CD57 + T-cells, CD57 + T-cell degranulation and CD34 + BM cell directed cytotoxicity. 34,35 Specific MDSC-targeting in MDS has so far been aiming at CD33-expressing cells. 36 So far, BI 836858 (Fc-engineered anti-CD33 moAb) for antibody-dependent cell-mediated cytotoxicity by NK-cells is currently tested in MDS patients in an ongoing Phase I/II clinical trial (ClinicalTrials.gov Identifier: NCT02240706).…”
Section: Myelodysplastic Syndromesmentioning
confidence: 99%